Improving the substrate binding of acetyl-CoA carboxylase (AccB) from Streptomyces antibioticus - Ali, Imtiaz; Wei, Dong-Qing; Khan, Abbas *; Feng, Yuanyuan; Waseem, Muhammad; Hussain, Zahid; Iqbal, Arshad; Ali, Syed Shujait; Mohammad, Anwar; Zheng, Jianting (Wiley, 2024)
Malonyl-CoA serves as the main building block for the biosynthesis of many important polyketides, as well as fatty acid–derived compounds, such as biofuel. Escherichia coli, Corynebacterium gultamicum, and Saccharomyces cerevisiae have recently been engineered for the biosynthesis of such compounds. However, the developed processes and strains often have insufficient productivity. In the current study, we used enzyme-engineering approach to improve the binding of acetyl-CoA with ACC. We generated different mutations, and the impact was calculated, which reported that three mutations, that is, S343A, T347W, and S350W, significantly improve the substrate binding. Molecular docking investigation revealed an altered binding network compared to the wild type. In mutants, additional interactions stabilize the binding of the inner tail of acetyl-CoA. Using molecular simulation, the stability, compactness, hydrogen bonding, and protein motions were estimated, revealing different dynamic properties owned by the mutants only but not by the wild type. The findings were further validated by using the binding-free energy (BFE) method, which revealed these mutations as favorable substitutions. The total BFE was reported to be −52.66 ± 0.11 kcal/mol for the wild type, −55.87 ± 0.16 kcal/mol for the S343A mutant, −60.52 ± 0.25 kcal/mol for T347W mutant, and −59.64 ± 0.25 kcal/mol for the S350W mutant. This shows that the binding of the substrate is increased due to the induced mutations and strongly corroborates with the docking results. In sum, this study provides information regarding the essential hotspot residues for the substrate binding and can be used for application in industrial processes.